Enhancing Entrepreneurial Literacy Through Mosque-Based Programs at Abu Adenan Mosque, Karangpilang Surabaya - Timur, Yan Putra; Ridlwan, Ahmad Ajib; Fikriyah, Khusnul; Susilowati, Fitriah Dwi (Indonesian Journal of Society Development, 2024)
This community service programme was carried out at the Abu Adenan Mosque, which is located in Kedurus Village, Karangpilang District, Surabaya City. The implementation includes several stages, starting from problem identification and ending with the preparation of the report. The activity was carried out face-to-face in the mosque, where the event was attended by a number of participants of approximately 27 people, consisting of the mosque Takmir, worshipers, and the community around the mosque. This international community service aimed to increase the participants' understanding of the importance of Islamic entrepreneurship principles and foster their aspirations to become successful Muslim entrepreneurs. One of the main outcomes observed was the increased interest and knowledge of the community in the field of entrepreneurship. Through a series of educational sessions and interactive workshops, participants gained a deeper understanding of the entrepreneurial mindset, basic business concepts, financial management, and Islamic marketing strategies. The materials provided emphasised entrepreneurial principles that are aligned with Islamic values, providing participants with insights on how to run an ethical and halal business